CHAID model of tourists expenditure pattern (Melaka UNESCO World Heritage Site) - Ab Rahman, Syakir Amir (2020)
A model created by Chi-Squared Automatic Interaction Detection (CHAID) for domestic and inbound tourists' expenditure patterns in Melaka UNESCO World Heritage Site.